2006
DOI: 10.1051/0004-6361:20053615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of high temporal resolution spectroscopic observations of flares on AD Leonis

Abstract: We report the results of a high temporal resolution spectroscopic monitoring of the flare star AD Leo. During 4 nights, more than 600 spectra were taken in the optical range using the Isaac Newton Telescope (INT) and the Intermediate Dispersion Spectrograph (IDS). We observed a large number of short and weak flares occurring very frequently (flare activity > 0.71 h We estimated the physical parameters of the flaring plasma by using a procedure that assumes a simplified slab model of flares. All the obtained ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 62 publications
8
54
3
Order By: Relevance
“…This is larger than the typical short-term Hα variations (of a factor of two in Δt ≤ 1 h) observed on M dwarfs (e.g. Crespo-Chacón et al 2006;Lee et al 2010;Kruse et al 2010). These differences are probably due to the much shorter timescales examined in these latter studies and observational biases in our sample in favor of UCDs that have caught attention because of their flaring activity either in Hα or X-rays.…”
Section: Observed Balmer Decrementsmentioning
confidence: 64%
“…This is larger than the typical short-term Hα variations (of a factor of two in Δt ≤ 1 h) observed on M dwarfs (e.g. Crespo-Chacón et al 2006;Lee et al 2010;Kruse et al 2010). These differences are probably due to the much shorter timescales examined in these latter studies and observational biases in our sample in favor of UCDs that have caught attention because of their flaring activity either in Hα or X-rays.…”
Section: Observed Balmer Decrementsmentioning
confidence: 64%
“…For the He i lines at 3819.6, 4026.2, and 6678.1 Å the line amplitudes are not strong enough to reveal a broad component, although the latter at least shows a second component. These broad component has been noted mostly in M-dwarf flares (Crespo-Chacón et al 2006;Fuhrmeister et al 2008Fuhrmeister et al , 2011, but also for young K-dwarfs (Montes et al 1999 and references therein). They can be blue-or (more often) red-shifted, and are often ascribed to a moving turbulent plasma component.…”
Section: Broad Line Componentsmentioning
confidence: 84%
“…Other flare studies usually concentrate on high resolution or high cadence; e.g. Crespo-Chacón et al (2006) studied flares on AD Leo with a cadence of typically 3 min, but with R of ∼3500 in the wavelength range of 3500 to 5176 Å. Also Kowalski et al (2010) observed a white light mega-flare on YZ CMi with a resolving power below 1000 but a cadence of 30 s covering a wavelength range from 3350 to 9260 Å.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the H α line peaks approximately 2.5 minutes before both Ca ii H & K lines. In an analysis of several flares on AD Leo, Crespo-Chacón et al (2006) find that the flare peaks in the Ca ii H & K lines were delayed with respect to that of the Balmer lines by up to 5 ± 3 min; in particular, this refers to the delay of the Ca ii K line with respect to H β. If anything, our observation indicates a similar trend.…”
Section: Evolution Of the Balmer And Ca II Linesmentioning
confidence: 98%
“…Similarly, Johns-Krull et al (1997) report on a GOES M7.7 class solar flare also finding the He i D3 line to be in absorption throughout the entire event and absent during quies-During flares on other stars the He i D3 line has been observed in emission. For instance, Crespo-Chacón et al (2006) detect the line studying flares on the active M-type star AD Leo and Montes et al (1999) report He i D3 emission during a flare on the K2 dwarf LQ Hya. Our observations indicate a potential small increase in the He i D3 flux during the rise phase of the flare, which would be consistent with observations of strong flares on the Sun, thereafter a phase of increasing absorption follows.…”
Section: The Behavior Of He I D3mentioning
confidence: 99%